Trouble in Utopia : the overburdened polity of Israel - Horowitz, Dan.; Lissak, Moshe, 1928-2018. (Albany : State University of New York Press, 1989)
Annotation A translation from the Hebrew manuscript which was completed in 1987. The authors' preface refers briefly to events of 1988. The work provides a detailed examination of Israeli institutions and how they function, explaining the decline in effectiveness of the government and the spread of cultural malaise in the Israel of the eighties. Paperback edition (unseen), $19.95. Annotation copyrighted by Book News, Inc., Portland, OR.
Includes bibliographical references (pages 319-346) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Israel -- Politics and government; Israel -- Ethnic relations; Social conflict -- Israel; Arab-Israeli conflict; Israël -- Politique et gouvernement; Conflit israélo-arabe.; SOCIAL SCIENCE -- Anthropology -- Cultural; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Popular Culture; Arab-Israeli conflict; Ethnic relations; Politics and government; Social conflict; Israel